Penerapan Pendekatan Metakognitif untuk Meningkatkan Kemampuan Berpikir Logis Matematis Siswa pada Materi sistem Persamaan Linear Dua variabel - Adjis, Vidia Amalia; Ruhama, Mustafa A.H.; Hamid, Hasan (Universitas Khairun, 2021)
The purpose of this research is to find out: 1) The mathematical logical thinking ability of grade VIII-9 Junior high School 4 Ternate after being set up a metacognitive approach to SPLDV material, 2) Enhancement of Mathematical logical thinking ability of grade VIII-9 Junior high School 4 city Ternate after the metacognitive approach to material SPLDV, and 3) How to improve the mathematical logical thinking skills of Grade VIII-9 Junior high School 4 City In Ternate after being established a metacognitive approach to SPLDV materials. The design of this research is experimental research with the model of one group pretests posttest design. The sample in this study was a class VIII-9 student, numbering 31 people. The instrument used to collect data is a test of the mathematical logical thinking ability of students. Test requirement analysis is done by testing the normality. Data were analyzed using descriptive statistical analysis and inferential statistical analysis. The results of research suggest that: 1) Logical thinking ability of mathematics grade VIII-9 Junior high School 4 Ternate City after the metacognitive approach to system material two-variable linear equations obtained 6 students in the high category, 3 students in the medium category, and 16 students in the low category. 2) There is an increase in mathematical logical thinking ability of grade VIII-9 Junior high School 4 Ternate after the implementation of a metacognitive approach to system material of two-variable linear equations. 3) enhancement of mathematical logical thinking skills of the students of grade VIII-9 Junior high School 4 Ternate after being set up a metacognitive approach on the system material of two-variable linear equations are interpreted.